Digital Literacy to Strengthen Character Education in the Society 5.0 Era at Sdn 1 Kertasura - Merakati, Indah; Nuryani, Dewi Eli (Jurnal Pengabdian Kepada Masyarakat Untukmu Nusantara, 2025)
This article is a summary of research on the importance of digital literacy for character development in the social era 5.0. The introduction of digital literacy is a very important tool that exists at every level of education, courses, and many forms of instruction in various fields. Various functions and aspects of national level education are emphasized in this context and seen as appropriate outcomes. In the era of Society 5.0, digital literacy is very important to use, empowering the population to develop the social and intellectual skills needed to support various issues related to the nation. Society 5.0 provides an example of how data can be used to mobilize and connect to any situation, including solving social problems. Basically, starting from children are required to have the skills necessary for society 5.0, such as: leadership, digital skills, communication, emotional intelligence, entrepreneurship, and global citizenship. . The aim of the Community Service Program (KKN) is to apply it as a form of education both theoretically and practically so that it can be applied well in a particular area. KKN activities can also be used as an opportunity for students as intellectuals to learn and provide solutions to social problems that occur in society. Kertasura village is a village located in the northern part of Cirebon district which borders directly with Inderamayu district, West Java. Based on the results of field observations, Kertasura village has very diverse potential in various sectors, such as the fisheries sector, agriculture, potential for the micro and medium enterprise (MSME) sector and the education sector